Competencia de la economía sumergida: puestos de trabajo en peligro? - Hadibi Zahir; Mohamed Saïb Musette (Atlantic Review of Economics (ARoEc), 2018)
– A review of the mode of regulation of the labor market regulation is expected according to the new "labor law" - in circulation for some time. The debate remains open as to the "illegalization" of informal job or the "formalization" of the informal economy. Informal employment (not affiliated with social security) is estimated at 4.3 million according to the 2017 ONS Labor Survey. This economy contributes around 35% to GDP formation. These findings call for a deep diagnosis before making any decision. What is know about this economy? What approach to adopt to avoid social tensions in the labor market? The proposed analysis is based on a series of reports, studies and theses on the labor market and on the informal sector in particular as well as a piece of news the exploitation of the statistical data and the statutory texts realized since the 2000s up this day. This reflection argues for a gradual regulation of the functioning of the labor market. The segmentation performed is an operational technical procedure, it is the reconstruction of the entire market, with its external ramifications, that can give its dynamic intelligence. Any "improvised" action can only exacerbate social tensions that would further undermine workers and employers and the economy in general.
Keywords: E26; O17; J21; 330; Informal economy; Informal employment; Algeria; Sociology of the informal